Redesigning university of the future in the digital era: humanising education and mental health - Azizan, Adiz Nabawi; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2020)
Mental health has been a rising problem in the current era and the cases reported are increasing every year. Thus, this issue needs to be addressed before it became a cancer to the societies. Many people do not think highly regarding the mental issues, but it was the root cause of any crimes and suicides. This paper tries to offer a new business model for a Malaysian-based university, named Malaysia – University of the Future (MY-UotfF), in providing humanising education as well as strengthening its role in community engagement and transformation activities. This study adapted the design thinking and system thinking approach that involve conducting literature review and interviews in understanding problems; analysing and formulating of business model options using business modelling tools such as Business Model Canvas (BMC) and Value Proposition Design Canvas (VPCs); and validation of the business model options via interviews with stakeholders. This programme is developed based on the BMC approach which looks at the customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structures. The key contribution of this paper is a conceptual business model for Malaysia – University of the Future – in the form of validated BMC and VPCs, for implementing and realising the humanising education programmes in MY-UotF. This paper also contributed on how to educate students in MY-UotF to become balanced graduated with healthy mental health and hence contributing to a harmonious and well-being of the community.